The risk of bleeding with anticoagulant treatments - Palareti, G. (Phlebologie, 2011)
Anticoagulant treatments are given to prevent and/or treat thrombotic complications in many clinical conditions, including atrial fibrillation (the most frequent indication for anticoagulant treatment), venous thromboembolism, acute coronary syndromes and after invasive cardiac procedures. Anticoagulation with vitamin K antagonists (VKAs) is currently almost the unique kind of therapy for chronic anticoagulation. It is highly effective in the prevention or treatment of thrombotic events but it is associated with a non negligible risk of bleeding, that is the most important complication of this therapy and a major concern for both physicians and patients. The risk of bleeding and the difficulties for the patients and health care providers associated with the necessary correct management of this treatment are limiting factors for a more widespread prescription of the treatment, leaving without an effective therapy a significant proportion of patients who would have a clear clinical indication for chronic anticoagulation. This review analyses the treatment- and person-associated risk factors for bleeding during VKAs and the tools that have been proposed to assess the individual risk of bleeding. New oral anticoagulant drugs seem to overcome at least some of the limitations of VKAs. Potentially, they can allow a less demanding and more stable anticoagulant treatment, with less side-effects allowing that more patients can receive an appropriate anticoagulant treatment. Based on the so far available phase III clinical studies, it is possible to assume that also these new drugs are associated with a risk of bleeding, that is probably related to the intensity of treatment.
Keywords: Anticoagulation; bleeding; vitamin K antagonists; new oral anticoagulants